Research on the remaining life prediction technology of environmentally friendly gas switchgear based on approximate dynamic programming - Zhang, Ziyu; Ye, Yirong; Xue, Lin; Tang, Baofeng; He, Lei; Zhao, Hongtao; Zhang, Pengliang; Sun, Shengxia; Fan, Jie (Frontiers in Energy Research, 2024)
The transformation of energy structure has brought about new changes in the power system, and the environmentally friendly gas switchgear with the goal of low carbon and environmental protection has been widely spread and applied, but due to its short application time and the accumulation of related research, it continues to carry out life prediction to improve the related operation and maintenance system. The article proposes the environmental protection gas switchgear data processing technology based on data enhancement technology, proposes the environmental protection gas switchgear life prediction technology based on approximate dynamic planning, and verifies the algorithm through case analysis, which proves the effectiveness and accuracy of the proposed method.